Workshop Pembelajaran Matematika Berbasis Budaya Melalui Batik Giriloyo, Wukirsari, Imogiri, Bantul - Ahmad Anis Abdullah; Muhammad Najib Mubarok; Robiatul Adawiya; Dyahsih Alin Sholihah; Rino Richardo; Duwik Nur Cahyo (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
Indonesia has cultural heritage that needs to be preserved, one of which is batik. This community service activity aims to introduce students participating in the Independent Student Exchange (PMM) Inbond Bach 3 Alma Ata University to the history of Giriloyo batik, the practice of batik, and analyzing the mathematical concepts contained therein. The methods used include planning,implementation and evaluation. The results of this activity show that students are able to know the history of batik, make batik, and analyze the mathematical concepts contained in batik motifs.